INTEGRATING PERTINENT ELEMENTS OF CRITICAL THINKING AND MATHEMATICAL THINKING USED BY PRACTICING CIVIL ENGINEERS IN GROUNDED THEORY ANALYSIS - Osman, Sharifah (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
This paper explains process of integrating the pertinent elements of critical thinking and mathematical thinking using Straussian grounded theory methodology. The process of integrating the pertinent elements occurs during selective coding process in the grounded theory analysis. Findings from open coding and axial coding process are the main source of information for development of the selective coding. The selective coding process employs the reflective coding matrix to develop and contextualize the core category. The refined core category depicts the process theory of justifying decision reasonably in dominating orientation. A conditional matrix is then developed as a coding device to visualize the process theory. The study contributes useful information to engineering education instructions, which is aligned with the expectations of engineering program outcomes set by the Engineering Accreditation Council.